Post-weaning growth performance of the Ashanti black pig under Intensive management system - Sarpong, Peter Kwasi (University of Cape Coast, 2009)
The post weaning growth performance of the Ashanti Black pig (ABP) at National Pig Breeding Station at Babile in the Upper West Region of Ghana was assessed. The records of 211 weaners over a seven-year period (1999-2005 inclusive) were used in the study. The influence of year of birth, sex and size of litter at weaning on performance traits – weaning weight at 42 days, body weights at 120 days, at 180 days and at 240 days of age and post weaning growth rates were investigated. All the traits studied were significantly (p<0.05) influenced by the effect of the year of birth, sex and litter size at weaning. The average performance levels attained during the study were weaning weight of 5.9 kg ± 0.08, body weight of 12.7 kg ± 0.2 at 120days, body weight of 17.7 kg ±0.3 at 180 days and body weight of 24.1 kg ±0.48 at 240 days. The average post weaning growth (PWG) rates measured from weaning to 120 days (PWG1), from weaning to 180days (PWG2) and from weaning to 240days (PWG3) were 87.1g/day ±2.2, 86.0g/day ± 2.2 and 92.0g/day ± 2.38 respectively. From the study, the post weaning growth performance of the ABP under intensive management is very encouraging as they compare well with other breeds of pigs under the local conditions. It has further added to the documentation of the performance of the breed which was hitherto non-existent. There is therefore the need to preserve the breed under such system of production to bring out its potential to become a national breed for use in commercial pork production in Ghana.
x,62p:,ill.
Keywords: Post weaning; Growth performance; Ashanti Black pig